Surficial placer gold deposits - Mann, P L (Rhodes University, Faculty of Science, Department of Geology, 1994)
This review summarises the factors which control the formation and distribution of surficial gold placer deposits. Regional tectonic and climatic conditions as well as gold source are considered. The characteristics of eluvial, alluvial, marine, glacial and fluvioglacial gold placer deposits are described. Particular attention is paid to the gold grains within these placers. These gold grains have a distinctive morphology and chemical composition which reflect the manner in which they were transported, deposited and concentrated within the placers. The knowledge of the processes which lead to the formation and location of surficial gold placers is then used to guide exploration and target potential deposits, which can then be evaluated.
Keywords: Gold mines and mining; Gold ores -- Geology; Placer deposits